Farm Animals Diseases, Recent Omic Trends and New Strategies of Treatment 2018
DOI: 10.5772/intechopen.74008
|View full text |Cite
|
Sign up to set email alerts
|

Avian Coccidiosis, New Strategies of Treatment

Abstract: The control of avian coccidiosis since the 1940s has been associated with the use of ionophores and chemical drugs. Recently, a significant interest in natural sources has developed due to the pressure to poultry industry to produce drug-free birds. Consequently, the search of products derived from plants and other natural sources has increased in the last years. Today, many commercial products containing essential oils, extracts, and other compounds are available. The use of these compounds of natural origin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Our results are in agreement with those of previous investigations, showing the efficacy of plant extracts against mixed or individual Eimeria infections, which can be used as potential anticoccidials in broiler chickens [ 60 ]. In addition, another study suggested the use of a combination of plant extract multi-compounds induces a good response, as an immunostimulatory effect, to destroy the oocyst of Eimeria or interfere with their life cycle [ 61 ]. It has also been reported in the literature that phenolic components demonstrate a wide range of biological properties, such as antibacterial, anticancer, antiproliferative, and anti-inflammatory properties [ 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our results are in agreement with those of previous investigations, showing the efficacy of plant extracts against mixed or individual Eimeria infections, which can be used as potential anticoccidials in broiler chickens [ 60 ]. In addition, another study suggested the use of a combination of plant extract multi-compounds induces a good response, as an immunostimulatory effect, to destroy the oocyst of Eimeria or interfere with their life cycle [ 61 ]. It has also been reported in the literature that phenolic components demonstrate a wide range of biological properties, such as antibacterial, anticancer, antiproliferative, and anti-inflammatory properties [ 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…A lot of natural herbs and their extracts were also practiced against coccidiosis like Trachyspermum ammi (Ajwain) by Abbas et al [13] but they have no significance as compared to chemotherapy. These compounds can act a little against some Eimeria species but not all due to huge genetic variability, which degrades their effect [14,15].…”
Section: Resistancementioning
confidence: 99%
“…Eimeria tenella is one of the most pathogenic protozoan parasites of the genus Eimeria, causing chicken coccidiosis worldwide (Quiroz-Castañeda, 2018). E. tenella infection is known to occur in the medial and distal parts of the chicken's cecum (Matsubayashi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%